A family affair: Library opportunities to connect with parents and families. Issue 4 (1st October 2016) - Benjamin, Laura M.; Dermody, Melinda
ABSTRACT: Parents are important aspects of our students' academic lives, and as such, should be acknowledged and considered as allies and potential partners with libraries. This article presents ideas for many ways in which libraries can engage with parents and families, while also exploring the benefits of such efforts. The broad areas in which these efforts fall include 1) overall student success, 2) connecting with other student-supporting and student-reaching entities on campus, and 3) supporting the critical efforts of student recruitment and retention. In this article, examples of different parent engagement opportunities are also discussed, including involvement in campus events, engaging with parent associations, considerations of legacy engagement, and collaboration with other campus units. The results of these parent-library initiatives and connections can help accomplish a variety of things including supporting student academic success, ensuring that the library is involved in other university student outreach efforts, contributing to development and fundraising activities and finally, supporting the recruitment and retention of students.